Heart rate fluctuation predicts mortality in critically ill patients in the intensive care unit: a retrospective cohort study - Guo, Qi (Ann Transl Med, 2021)
BACKGROUND: To evaluate the association between heart rate (HR) fluctuation and mortality in critically ill patients in the intensive care unit (ICU). METHODS: A total of 27,814 patients were enrolled from the Medical Information Mart for Intensive Care database and were divided into 3 groups: low HR fluctuation [<25 beats per minute (bpm)], control (25–34 bpm), and high HR fluctuation (≥35 bpm), based on the initial 24-hour HR fluctuation (calculated as the maximum HR minus minimum HR). Multivariate Cox regression and restricted cubic spline models were used. RESULTS: Compared to the control group, higher risk of 28-day and 1-year mortality remained significant in an adjusted model, with hazard ratios of 1.210 [95% confidence interval (CI), 1.103–1.327] and 1.150 (95% CI, 1.078–1.227), respectively, in the high HR fluctuation group, as well as hazard ratios of 1.130 (95% CI, 1.035–1.232) and 1.087 (95% CI, 1.022–1.157), respectively, in the low HR fluctuation group. Restricted cubic splines showed a U-type curve, with the lowest risk of mortality at an HR fluctuation of 30 bpm. CONCLUSIONS: This retrospective cohort study revealed that both high and low HR fluctuation correlated with increased mortality in critically ill ICU patients, providing new insights for optimizing HR control strategies.